2012
DOI: 10.1653/024.095.0128
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial COI fromDysmicoccus brevipes(Hemiptera: Pseudococcidae) Suggests Cryptic Lineage and Pinpoints the Source of the Introduction to China

Abstract: The pink pineapple mealybug, Dysmicoccus brevipes (Cockerell) (Hemiptera: Pseudococcidae), is a widespread plant-sucking insect of considerable concern because it transmits the pineapple mealybug wilt-associated virus. The purpose of this study was to use molecular methods to clarify the relationship among pink pineapple mealybugs from China, Philippines, Thailand and Hawaii, in an effort to determine the geographic origin of the introduction to China. Pink pineapple mealybug samples were collected from 10 cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…PPM is ovoviviparous and reproduces parthenogenetically in most areas as a wingless insect, and the female mealybug is normally distributed whilst hiding in the seedlings (He et al, 2012). Phylogenetic analyses suggest that there are close genetic relationships between PPM populations from Hawaii, Brazil, the Philippines, and from some resources from Thailand and China, and that they all probably originate from South America.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPM is ovoviviparous and reproduces parthenogenetically in most areas as a wingless insect, and the female mealybug is normally distributed whilst hiding in the seedlings (He et al, 2012). Phylogenetic analyses suggest that there are close genetic relationships between PPM populations from Hawaii, Brazil, the Philippines, and from some resources from Thailand and China, and that they all probably originate from South America.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analyses suggested that the source of D. brevipes in Hawaii was likely to be the mealybug lineage that lives predominantly in Brazil, Thailand, and the Philippines, according to the sequences of mitochondrial cytochrome c oxidase subunit I (COI) downloaded from GenBank. However, phylogenetic analyses also showed that PPMs from China are of different geographic origin to the samples from Hawaii (He et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Zhao 等 人 [72] 、Ahmed 等人 [73] 和 Wu 等人 [74] 对我国其他地区 和国外部分种群的分析验证了先前的推测, 并表明 我国不同地理种群的扶桑绵粉蚧其遗传差异较小; 中国、印度、巴基斯坦和美国加州的种群构成一个支 系, 美国佛罗里达州的种群为另一支系. 此外, He 等 人 [75] 还探讨了菠萝洁粉蚧种群的遗传多样性, 发现 我国的菠萝洁粉蚧存在 3 种单倍型, 其中海南万宁种 群可能是其中的一个隐存谱系, 而大陆单倍型与菲 律宾种群相近; 推测我国 20 世纪初从东南亚大量引 进种植菠萝(Ananas comosus)可能无意使菠萝洁粉蚧 借机入侵大陆, 为入侵害虫菠萝洁粉蚧的溯源提供 了依据.…”
Section: 在介壳虫类昆虫研究中的应用unclassified